2020
DOI: 10.1093/mnras/staa2713
|View full text |Cite
|
Sign up to set email alerts
|

New H2O–H2O collisional rate coefficients for cometary applications

Abstract: We re-introduce a semi-classical methodology based on theories developed for the determination of broadening coefficients. We show that this simple and extremely fast methodology provides results that are in good agreement with results obtained using the more sophisticated MQCT approach. This semi-classical methodology could be an alternative approach which allows to provide large sets of collisional data for very complex molecular systems. It saves time both on the determination of potential energy surfaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 49 publications
4
41
3
Order By: Relevance
“…55 We found, however, that the adaptive step-size control routine gave advantage only for the molecular systems with a long-range interaction potential, such as H 2 O + H 2 O. 31,36,41 For other cases, such as the H 2 O + H 2 system considered here, the "black-boxed" step-size control gave no noticeable increase of performance. However, we realized that the adiabatic trajectory approximation introduced above gives us an opportunity to implement a very efficient method for the variable-step integration of the quantum system of equations, eq 5, propagated during the second step of the AT-MQCT calculations (which is the only costly part of new method).…”
Section: ■ Theorymentioning
confidence: 85%
See 3 more Smart Citations
“…55 We found, however, that the adaptive step-size control routine gave advantage only for the molecular systems with a long-range interaction potential, such as H 2 O + H 2 O. 31,36,41 For other cases, such as the H 2 O + H 2 system considered here, the "black-boxed" step-size control gave no noticeable increase of performance. However, we realized that the adiabatic trajectory approximation introduced above gives us an opportunity to implement a very efficient method for the variable-step integration of the quantum system of equations, eq 5, propagated during the second step of the AT-MQCT calculations (which is the only costly part of new method).…”
Section: ■ Theorymentioning
confidence: 85%
“…Inelastic collisions of molecules with atomic gasses with other gas-phase molecules or with solid surfaces lead to the energy exchange between translational, rotational, and vibrational degrees of freedom, which is a fundamentally important phenomenon in the field of chemical physics. On the applied side, the inelastic molecular collisions play critical roles in many processes that span a huge range of sizes and time scales from the man-made microtraps to the galaxy and extra-galactic sizes. Therefore, theoretical prediction of inelastic cross sections has been and still is actively pursued, including practical applications of well-known codes to more and more complex molecular processes, ,,, development of new computational tools, and exploration of new theoretical methodologies. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comets, the excitation of molecules is usually dominated by collisions with H 2 O. Several studies involving collisions with water molecules can be found in the literature, from which the collisional systems of H 2 O-H 2 O, [8][9][10] and H 2 O-CO, 7 have the most significant impact for modeling cometary spectra. An important exception is the case of comets at large heliocentric distances, for which the production of gaseous CO is larger than H 2 O.…”
Section: Introductionmentioning
confidence: 99%